PENGARUH IMPLEMENTASI UPCYCLING DALAM MEMBUAT SCRUNCHIE TERHADAP KREATIVITAS ANAK DI PANTI ASUHAN SYUKUR ANAK INDONESIA, MEDAN - Eirene Zai, Ribka; Kurniawan, Fauzi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Children's creativity is an ability that needs to be developed from an early age. However, the creativity of children at Syukur Anak Indonesia Orphanage, Medan, has not yet developed optimally. Therefore, this study aimed to determine the effect of implementing upcycling through making scrunchies on children's creativity at Syukur Anak Indonesia Orphanage, Medan. This study employed a quantitative approach using an experimental method with a One Group Pretest-Posttest Design. The population consisted of 36 children, while the sample comprised 22 children aged 7–15 years selected through purposive sampling. The research instrument was a creativity test developed based on four aspects of creativity: fluency, flexibility, originality, and elaboration. Data were analyzed using a normality test and hypothesis testing through a paired sample t-test. The results showed that the children's creativity score increased from 1,208 in the pretest to 1,687 in the posttest, representing an increase of 479 points or 39.65%. Improvements occurred across all creativity aspects, namely fluency (29.48%), flexibility (20.86%), originality (62.27%), and elaboration (51.67%). The hypothesis test yielded a significance value of 0.000 < 0.05 and a calculated t-value of 7.697, indicating that Ha was accepted and H₀ was rejected. Therefore, the implementation of upcycling through making scrunchies had a significant effect on children's creativity at Syukur Anak Indonesia Orphanage, Medan.